EXPRESSION OF CONCERN: CircZNF124 regulates cell proliferation, leucine uptake, migration and invasion by miR‐199b‐5p/SLC7A5 pathway in endometrial cancer - Liuping Shu; Yan Peng; Liyan Zhong; Xi Feng; Lifu Qiao; Yi Yi (Immunity, Inflammation and Disease)
Abstract Background Recent studies have revealed that circular RNA participates in endometrial carcinoma (EC) progression. Here we investigated the role of circRNA zinc finger protein 124 (circZNF124) in EC genesis and underlying mechanism. Methods The expression levels of circZNF124, microRNA‐199b‐5p (miR‐199b‐5p) and solute carrier family 7 member 5 (SLC7A5) were detected by quantitative real‐time polymerase chain reaction. The expression of SLC7A5 and other indicated marker proteins was determined by western blot analysis. For functional assay, cell proliferation, leucine uptake and metastasis were investigated by total cell number, cell counting kit‐8, cell colony formation, leucine uptake or transwell assay. The interaction between miR‐199b‐5p and circZNF124 or SLC7A5 was predicted by starbase online database, and identified by mechanism assays. The impact of circZNF124 absence on tumor growth in vivo was revealed by xenograft mouse model assay. Immunohistochemistry assay was implemented to detect the positive expression rate of nuclear proliferation marker (Ki67). Results CircZNF124 and SLC7A5 expression were significantly increased, while miR‐199b‐5p was decreased in EC tissues and cells compared with normal endometrial tissues or cells. CircZNF124 expression was closely associated with EC severity and lymph node metastasis. Additionally, circZNF124 depletion repressed cell proliferation, leucine uptake, migration and invasion in both HEC1A and Ishikawa cells. CircZNF124 regulated SLC7A5 expression by binding to miR‐199b‐5p. MiR‐199b‐5p inhibitors or SLC7A5 overexpression attenuated circZNF124 silencing‐mediated EC malignant progression. Furthermore, SLC7A5 absence inhibited tumor growth in vivo. Conclusion CircZNF124 depletion inhibited EC cell malignancy by miR‐199b‐5p/SLC7A5 pathway, which demonstrated that circZNF124 had the potential as a therapeutic target for EC.